2019
DOI: 10.3390/cells8091077
|View full text |Cite
|
Sign up to set email alerts
|

Deregulated miR-29b-3p Correlates with Tissue-Specific Activation of Intrinsic Apoptosis in An Animal Model of Amyotrophic Lateral Sclerosis

Abstract: Amyotrophic lateral sclerosis (ALS) is one of the most common incurable motor neuron disorders in adults. The majority of all ALS cases occur sporadically (sALS). Symptoms of ALS are caused by a progressive degeneration of motor neurons located in the motor cortex and spinal cord. The question arises why motor neurons selectively degenerate in ALS, while other cells and systems appear to be spared the disease. Members of the intrinsic apoptotic pathway are frequent targets of altered microRNA expression. There… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 148 publications
(175 reference statements)
2
17
0
Order By: Relevance
“…Recently, the link between neuron degeneration in wobbler mice and the apoptotic pathways including caspase activity was investigated by the authors in [45]. Considering that caspase 3 and 6 were proven to show a coordinated activation in the apoptosis of cerebellar granule cells [60], the results within the mentioned study, such as an increased activeness of caspase 3, agree with previous assumptions [45].…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Recently, the link between neuron degeneration in wobbler mice and the apoptotic pathways including caspase activity was investigated by the authors in [45]. Considering that caspase 3 and 6 were proven to show a coordinated activation in the apoptosis of cerebellar granule cells [60], the results within the mentioned study, such as an increased activeness of caspase 3, agree with previous assumptions [45].…”
Section: Discussionsupporting
confidence: 76%
“…While there was found to be various pathological phenomena within the wobbler mouse, such as an enlargement of endosomal vesicles [ 11 ], an impairment of the anterograde and retrograde axonal transport [ 43 ] or a mitochondrial dysfunction [ 44 ], there is still a lack of investigations regarding the beginning of the degenerative causal chain. The Vps54 gene defect is not yet sufficient to explain all cellular pathologies within the wobbler motor neurons [ 10 , 45 ]. By isolating the cells of the ventral horn from remaining tissues and compartments of the organism, we were able to create standardized conditions and independence from potential systemic triggers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the primary objectives of this study was to determine whether disruption of scat expression in adult flies caused phenotypes like those observed in the wobbler mouse. While mutations in Vps54 have not been directly linked to human disease, the wobbler mouse has been used by many researchers as a model for the sporadic form of ALS because of striking similarities to ALS pathology ( Ikeda et al, 1998 ; Dennis and Citron, 2009 ; Nieto-Gonzalez et al, 2011 ; Moser et al, 2013 ; Dahlke et al, 2015 ; Schmitt-John, 2015 ; Klatt et al, 2019 ; Rohm et al, 2019 ; Cihankaya et al, 2021 ; De Nicola et al, 2021 ). It has previously been shown that scat mutants share spermatogenesis defects caused by Golgi dysfunction with the wobbler mouse ( Castrillon et al, 1993 ; Fari et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…In ALS mouse SCs, miR-29a is upregulated by the ER stress-induced TF ATF4 [ 126 ], causing the downregulation of the antiapoptotic factor Mcl-1 [ 127 ]. In the wobbler mouse, it was reported that miR-29b-3p overexpression downregulated the proapoptotic factors BAK, BAX, and BMF, leading to apoptosis and, thus, to neurodegeneration [ 128 ]. Li et al [ 129 ] demonstrated, instead, that the downregulation of miR-193b-3p—reported in sALS patients as well [ 130 ]—promoted cell death in the ALS SOD1 G93A mouse.…”
Section: Noncoding Rna Landscapementioning
confidence: 99%